Method for preparing nickel-iron-copper spinel coating

By preparing (Ni, Fe, Cu) 3O4 coating on stainless steel connectors by electroplating deposition and magnetron sputtering composite method, the problems of insufficient oxidation resistance and cathodic poisoning at high temperatures are solved, and higher oxidation resistance and service life are achieved.

CN119800460APending Publication Date: 2025-04-11NORTHEASTERN UNIV CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510028550.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Ferrite stainless steel has insufficient antioxidant performance and cathode poisoning caused by volatilization of Cr substances after working for a long time at high temperatures, which affects the high-temperature performance and service life of the battery.

Method used

(Ni, Fe, Cu) 3O4 coating was prepared on the surface of stainless steel connector by electroplating deposition and magnetron sputtering composite method, and a dense oxide film was formed by thermal conversion, which prevented the external diffusion of Cr and improved oxidation resistance.

Benefits of technology

It effectively improves the oxidation resistance and chemical stability of stainless steel connectors, significantly extends the service life of the battery, and enhances its high-temperature performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005233485480000011
    Figure HDA0005233485480000011
  • Figure HDA0005233485480000012
    Figure HDA0005233485480000012
  • Figure HDA0005233485480000013
    Figure HDA0005233485480000013
Patent Text Reader

Abstract

The invention is suitable for the field of solid oxide fuel cells, and relates to a method for preparing a nickel-iron-copper spinel coating. According to the invention, the Cu layer is prepared by using an electroplating deposition technology, and then the NiFe2 layer is continuously deposited on the surface by using a magnetron sputtering technology. And after high-temperature oxidation, carrying out thermal conversion on Cu-NiFe2 to obtain the (Ni, Fe, Cu) 3O4 coating. According to the method, the process is simple and easy to implement and environmentally friendly, the coating has few defects and is well combined with the matrix, the (Ni, Fe and Cu) 3O4 coating is obtained after thermal conversion, external diffusion of Cr in the matrix is effectively prevented, an oxidation film on the surface of the oxidized matrix has good conductivity, the oxidation resistance of the matrix is remarkably improved, and the service life of the matrix is prolonged. The method can be applied to a solid oxide fuel cell connector coating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid oxide fuel cells, and in particular to a solid oxide fuel cell metal connector with a (Ni, Fe, Cu) 3 O 4 coating and a method for preparing the coating. Technical Background

[0002] Solid oxide fuel cells (SOFCs) are third-generation fuel cells that can convert the chemical energy of fuels into electrical energy through electrochemical reactions. They are widely used due to their strong fuel adaptability, green and efficient, all-solid-state structure, and other advantages. SOFC applications are mainly concentrated in portable power supplies, distributed power generation / combined heat and power systems, large power stations, and other fields. Since the voltage provided by a single cell is limited, a connector is required to assemble the single cell into a battery stack to meet the power supply requirements. Therefore, the connector is one of the key components of solid oxide fuel cells. With the development of anode support technology, the operating temperature of the battery has been reduced to 600-800℃, making it possible to use metals instead of ceramic materials as connectors. Ferritic stainless steel matches the thermal expansion coefficient of other components of SOFC and has good oxidation resistance, so it is widely used as a metal connector material.

[0003] Although ferritic stainless steel performs well, it still has problems of insufficient antioxidant properties and cathode poisoning caused by the volatilization of Cr substances (such as CrO3 and CrO2(OH)2) after working for a long time at high temperature. Cathode poisoning will have a negative impact on the high temperature performance of the battery and reduce the battery life. Preparing a protective conductive coating on the surface of the connector can effectively solve the above problems. Currently, the coating materials suitable for SOFC ferritic stainless steel connectors mainly include rare earth perovskite type, active element oxide type, nitride type and spinel type. Among them, spinel type has good conductivity and a thermal expansion coefficient that matches other SOFC components. Studies have shown that the (Ni,Fe,Cu)3O4 coating exhibits good electrical properties, antioxidant properties and chemical stability in the SOFC working environment, and is a spinel coating material with excellent performance.

[0004] Methods for preparing (Ni,Fe,Cu)3O4 coatings on the surface of stainless steel connectors include: sol-gel method, electrophoretic deposition method, electroplating deposition method, plasma spraying method, magnetron sputtering method, etc. The coating obtained by electrophoresis is usually loose and porous, has poor bonding with the substrate and is easy to peel off; the sol-gel process has the problem of uneven film coating; the electroplating method has low cost for preparing coatings, simple operation, and the obtained coatings have few defects and good bonding with the substrate; the magnetron sputtering method can achieve rapid deposition of the coating and can accurately control the composition and thickness of the film. Therefore, the electroplating-magnetron sputtering composite method is used to obtain the (Ni,Fe,Cu)3O4 coating. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a (Ni, Fe, Cu) 3 O 4 coating and a preparation method thereof.

[0006] The specific technical solutions are as follows:

[0007] 1. The thickness of the Cu-NiFe2 layer is about 4.5 μm;

[0008] 2. A method for preparing a (Ni, Fe, Cu) 3 O 4 coating, characterized in that the method comprises the following steps:

[0009] (1) Pretreatment: Use 240#, 400#, 600#, 800#, 1000#, and 2000# SiC water-abrasive sandpaper to polish the surface of the ferritic stainless steel substrate, and perform edge grinding and chamfering. After polishing, ultrasonic cleaning is performed in acetone for 10 to 20 minutes. After 15 minutes, dry the sample, wash it in sodium carbonate solution for 10 minutes at 50°C, rinse it and dry it, ultrasonically clean it in dilute sulfuric acid solution for 30 seconds, take it out, rinse it and dry it;

[0010] (2) using distilled water as the solvent, potassium pyrophosphate and copper pyrophosphate as the solutes to prepare a stable electroplating solution, and using ammonia water and boric acid solution to adjust the pH value;

[0011] (3) depositing a metal Cu layer on the surface of the metal substrate using electroplating deposition technology;

[0012] (4) A NiFe2 alloy coating is deposited on the surface of a metal substrate using magnetron sputtering technology, and the specific steps are as follows: 1. Pre-sputtering: Pre-sputtering for 10 to 20 minutes to remove oxides and other impurities on the surface of the target material to ensure the stability of sputtering and the quality of the coating; 2. Sputtering NiFe2 alloy: The target material is an alloy target with a Ni:Fe atomic ratio of 1:2, and the NiFe2 alloy coating is obtained by sputtering deposition for 1h;

[0013] The sample with deposited Cu-NiFe2 coating was thermally converted at 800℃ to obtain (Ni,Fe,Cu)3O4 coating.

[0014] In the step (1), the acetone cleaning time is 10 to 15 minutes, the ultrasonic power is 80 to 100 W, and the Cr content in the matrix is ​​16 to 25 mass%.

[0015] The composition of the electroplating solution used for electroplating deposition in the step (2) is as follows: 200-250 g / L potassium pyrophosphate, 50-70 g / L copper pyrophosphate, 0.5-1 mL / L ammonia water, and 0.2-0.5 g / L boric acid.

[0016] The electroplating current density in step (3) is 5-15 mA / cm 2 The electroplating temperature is 40-60°C and the electroplating time is 30-90s.

[0017] The target-base distance in step (4.1) is 8 cm. First, turn on the mechanical pump to pre-pump to about 5 Pa, then turn on the diffusion pump to fine-pump to a vacuum of 5×10 -3 Pa; sputtering current 3.0A, sputtering pressure 0.1~0.15Pa, sputtering temperature 200℃, turntable speed 40~60r / min, sampling is carried out when the vacuum chamber temperature drops below 70℃.

[0018] The beneficial effects of the present invention are: The method of the present invention is simple and easy to implement and is environmentally friendly: the coating prepared by the electroplating method has fewer defects and is well bonded to the substrate; the sputtering rate is stable, and a SOFC connector coating with uniform thickness and accurate composition can be prepared, and the thickness of the coating can be adjusted by controlling the sputtering time; The prepared coating has a dense structure and good bonding with the substrate; after thermal conversion, a (Ni, Fe, Cu) 3 O 4 coating is obtained, which effectively prevents the outward diffusion of Cr in the substrate; after oxidation, the oxide film on the surface of the substrate has good electrical conductivity, which significantly improves the oxidation resistance of the substrate and can be used in solid oxide fuel cell connector coating materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The cross-sectional morphology of the stainless steel sample deposited with Cu-NiFe2 coating prepared in Example 1;

[0020] Figure 2 The cross-sectional morphology of the stainless steel sample deposited with Cu-NiFe2 coating prepared in Example 1 after oxidation for 5 minutes;

[0021] Figure 3 The cross-sectional morphology of the stainless steel sample deposited with Cu-NiFe2 coating prepared in Example 1 after oxidation for 10 minutes;

[0022] Figure 4 The surface morphology of the stainless steel sample deposited with Cu-NiFe2 coating prepared in Example 1 after oxidation for 1 week.

[0023] Figure 5 The cross-sectional morphology of the stainless steel sample with the deposited Cu-NiFe2 coating prepared in Example 1 after oxidation for 1 week. DETAILED DESCRIPTION

[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but the embodiments of the present invention are not limited thereto.

[0025] Embodiments of the present invention are as follows: Example 1: This example uses SUS430 stainless steel as the substrate (Cr: 20 mass%) This embodiment adopts the electroplating deposition and DC magnetron sputtering methods mentioned in the present invention to successfully prepare the Cu-NiFe2 coating material.

[0026] 1. Configure the plating solution for electroplating deposition:

[0027] The composition of the electroplating solution is as follows: 250 g / L potassium pyrophosphate, 70 g / L copper pyrophosphate, and 0.4 g / L boric acid.

[0028] 2. Matrix pretreatment:

[0029] This experiment uses stainless steel as the substrate, with a size of 15mm×10mm×2mm. Use 240#, 400#, 600#, 800#, 1000#, 2000# SiC water-abrasive sandpaper to grind the surface of the ferritic stainless steel substrate, and grind and chamfer it; after grinding, ultrasonically clean it in acetone for 10 to 15 minutes; after that, dry the sample, alkaline wash it in sodium carbonate solution for 10 minutes, and the alkaline washing temperature is 50℃; after rinsing and drying, ultrasonically clean it in dilute sulfuric acid solution for 30 seconds, take it out, rinse it, dry it and set it aside.

[0030] 3. Electroplating and depositing metal Cu layer on the substrate surface:

[0031] This experiment was carried out in a double-anode, single-cathode electrophoresis device. The process conditions for electroplating Cu were: electrophoresis time: 60s, current density: 15mA / cm 2 The electrophoresis temperature was 50°C.

[0032] 4. Sputtering NiFe2 alloy layer on the Cu-coated substrate surface, the steps are as follows:

[0033] 1. Pre-sputtering: Pre-sputtering for 10 to 20 minutes to remove oxides and other impurities on the surface of the target material to ensure the stability of sputtering and the quality of the coating; 2. Sputtering NiFe2 alloy: The target material is an alloy target with a Ni:Fe atomic ratio of 1:2, and the NiFe2 alloy coating is obtained by sputtering deposition for 1h;

[0034] Thermal conversion to obtain (Ni,Fe,Cu)3O4 coating: The stainless steel sample coated with Cu-NiFe2 coating was placed in a box-type resistance furnace at 800°C for high-temperature oxidation to obtain (Ni,Fe,Cu)3O4 coating.

[0035] Embodiments of the present invention are as follows: Example 2: This example uses SUS430 stainless steel as the matrix (Cr: 20 mass%) This embodiment adopts the electroplating deposition and DC magnetron sputtering methods mentioned in the present invention to successfully prepare the Cu-NiFe2 coating material.

[0036] 1. Configure the plating solution for electroplating deposition:

[0037] The composition of the electroplating solution is as follows: 250 g / L potassium pyrophosphate, 70 g / L copper pyrophosphate, and 0.4 g / L boric acid.

[0038] 2. Matrix pretreatment:

[0039] This experiment uses stainless steel as the substrate, with a size of 15mm×10mm×2mm. Use 240#, 400#, 600#, 800#, 1000#, 2000# SiC water-abrasive sandpaper to grind the surface of the ferritic stainless steel substrate, and grind and chamfer it; after grinding, ultrasonically clean it in acetone for 10 to 15 minutes; after that, dry the sample, alkaline wash it in sodium carbonate solution for 10 minutes, and the alkaline washing temperature is 50℃; after rinsing and drying, ultrasonically clean it in dilute sulfuric acid solution for 30 seconds, take it out, rinse it, dry it and set it aside.

[0040] 3. Electroplating and depositing metal Cu layer on the substrate surface:

[0041] This experiment was carried out in a double-anode, single-cathode electrophoresis device. The process conditions for electroplating Cu were: electrophoresis time: 60s, current density: 15mA / cm 2 The electrophoresis temperature was 50°C.

[0042] 4. Sputtering NiFe2 alloy layer on the Cu-coated substrate surface, the steps are as follows:

[0043] 1. Pre-sputtering: Pre-sputtering for 10 to 20 minutes to remove oxides and other impurities on the surface of the target material to ensure the stability of sputtering and the quality of the coating; 2. Sputtering NiFe2 alloy: The target material is an alloy target with a Ni:Fe atomic ratio of 1:2, and the NiFe2 alloy coating is obtained by sputtering deposition for 1h;

[0044] Thermal conversion to obtain (Ni,Fe,Cu)3O4 coating: The stainless steel sample coated with Cu-NiFe2 coating was placed in a box-type resistance furnace at 800°C for high-temperature oxidation to obtain (Ni,Fe,Cu)3O4 coating.

[0045] Embodiments of the present invention are as follows: Example 3: This example uses SUS430 stainless steel as the substrate (Cr: 20 mass%) This embodiment adopts the electroplating deposition and DC magnetron sputtering methods mentioned in the present invention to successfully prepare the Cu-NiFe2 coating material.

[0046] 1. Configure the plating solution for electroplating deposition:

[0047] The composition of the electroplating solution is as follows: 250 g / L potassium pyrophosphate, 70 g / L copper pyrophosphate, and 0.4 g / L boric acid.

[0048] 2. Matrix pretreatment:

[0049] This experiment uses stainless steel as the substrate, with a size of 15mm×10mm×2mm. Use 240#, 400#, 600#, 800#, 1000#, 2000# SiC water-abrasive sandpaper to grind the surface of the ferritic stainless steel substrate, and grind and chamfer it; after grinding, ultrasonically clean it in acetone for 10 to 15 minutes; after that, dry the sample, alkaline wash it in sodium carbonate solution for 10 minutes, and the alkaline washing temperature is 50℃; after rinsing and drying, ultrasonically clean it in dilute sulfuric acid solution for 30 seconds, take it out, rinse it, dry it and set it aside.

[0050] 3. Electroplating and depositing metal Cu layer on the substrate surface:

[0051] This experiment was carried out in a double-anode, single-cathode electrophoresis device. The process conditions for electroplating Cu were: electrophoresis time: 60s, current density: 15mA / cm 2 The electrophoresis temperature was 50°C.

[0052] 4. Sputtering NiFe2 alloy layer on the Cu-coated substrate surface, the steps are as follows:

[0053] 1. Pre-sputtering: Pre-sputtering for 10 to 20 minutes to remove oxides and other impurities on the surface of the target material to ensure the stability of sputtering and the quality of the coating; 2. Sputtering NiFe2 alloy: The target material is an alloy target with a Ni:Fe atomic ratio of 1:2, and the NiFe2 alloy coating is obtained by sputtering deposition for 1h;

[0054] Thermal conversion to obtain (Ni,Fe,Cu)3O4 coating: The stainless steel sample coated with Cu-NiFe2 coating was placed in a box-type resistance furnace at 800°C for high-temperature oxidation to obtain (Ni,Fe,Cu)3O4 coating.

[0055] The (Ni, Fe, Cu)3O4 coating prepared by the invention has good bonding strength with the substrate, without obvious gaps and holes. The (Ni, Fe, Cu)3O4 coating obtained after thermal conversion effectively prevents the outward diffusion of Cr in the substrate; the oxide film on the surface of the substrate after oxidation has good electrical conductivity, significantly improves the oxidation resistance of the substrate, and can be applied to the coating material of the connector of solid oxide fuel cells. The above embodiments are used to explain the present invention, rather than to limit the present invention. Within the spirit of the present invention and the protection scope of the claims, any modifications and changes made to the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a nickel-iron-copper spinel coating, characterized in that: The method specifically comprises the following steps: (1) preparing a plating solution for electroplating deposition; (2) using the electroplating solution prepared in step (1) to electroplatingly deposit a metal Cu layer on the surface of the metal substrate; (3) Using magnetron sputtering technology, a NiFe2 alloy layer is sputtered on the surface of the Cu-coated substrate after pre-sputtering and sputtering steps. (4) subjecting the metal substrate coated with the Cu-NiFe2 coating prepared in step (3) to high-temperature thermal oxidation to thermally convert the Cu-NiFe2 coating into a (Ni, Fe, Cu)3O4 coating.

2. The method for preparing nickel-iron-copper spinel according to claim 1, characterized in that The composition of the Cu layer electroplating solution used to prepare the Cu layer in step (1) is as follows: 200-250 g / L potassium pyrophosphate, 50-70 g / L copper pyrophosphate, 0.5-1 mL / L ammonia water, and 0.2-0.5 g / L boric acid.

3. The method for preparing a lanthanum chromate coating according to claim 1, wherein the process for preparing the Cu plating layer in step (2) is as follows: the current density is 5 to 15 mA / cm 2 , electroplating temperature 40 ~ 60 ℃, electroplating time 30 ~ 90s.

4. The method for preparing lanthanum chromate coating according to claim 1, wherein the target-substrate distance in step (3) is 8 cm. First, turn on the mechanical pump to pre-pump to about 5 Pa, then turn on the diffusion pump to fine-pump to a vacuum of 5×10 -3 Pa; sputtering current 3.0A, sputtering pressure 0.1~0.15Pa, sputtering temperature 200℃, turntable speed 40~60r / min, sampling is carried out when the vacuum chamber temperature drops below 70℃.

Citation Information

Cited By

  • Protective coating on surface of SOFC (solid oxide fuel cell) metal connector as well as preparation and application of protective coating

    CN122327146A